El Documentalista de Información de Actualidad. Formación y profesión - Baranda del Campo, Cristina (Cuadernos de Documentación Multimedia, 2009)
The suitable information of the documentalist is the overall aim of this research. The new resources, the new technologies and the proposing solutions that encourage the educational plans matters to the conjoint study of document and new forms of information. The journalist should be trained as a documentalist to be a complet journalist. With some intensive subjects or in a organized affluent course, it can extend its knowledge in new technologies, file and cataloguing. Nevertheless, the documentalist with its preparation, cannot defend by himself at the time of informing. Can manage the contents, but does not know how to treat them. The ideal preparation of the informer is the one that fuses the figures of the documentalist and journalist in a single one. The journalist will be able to make documentation tasks, whenever handles the suitable tools, whereas the documentalist, is limited when trying to exert of journalist. The specific aim is to try to define a study plan that achieve that the informer can know how to document itself by itself and the documentalist can inform with correction.